Interior design - Pile, John F; Friedmann, Arnold (Upper Saddle River, NJ : Pearson Prentice Hall, 2007)
"This book is concerned with the full range of interior design challenges, from the modest and everyday experiences at home and at work to full priofessional involvement in large projects." -- Preface pg. 11
Includes bibliographical references (p. 587-591) and index
Keywords: Interior decoration; Interior architecture